2021
DOI: 10.21037/qims-20-603
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of imaging parameters in chest CT for COVID-19 patients: an experimental phantom study

Abstract: Background: With the global outbreak of coronavirus disease 2019 (COVID-19), chest computed tomography (CT) is vital for diagnosis and follow-up. The increasing contribution of CT to the populationcollected dose has become a topic of interest. Radiation dose optimization for chest CT of COVID-19 patients is of importance in clinical practice. The present study aimed to investigate the factors affecting the detection of ground-glass nodules and exudative lesions in chest CT among COVID-19 patients and to find a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The routine chest CT protocol had been optimized in our radiology center to reduce the radiation dose of COVID-19 patients without reducing its efficiency. Several studies confirmed the effectiveness of low-dose and ultra-low-dose CT scans in detecting and evaluating COVID-19 [ 22 25 ]. Therefore, in pandemics such as COVID-19 where ionizing radiation is employed for screening or follow-up of a large population, radiation settings can be significantly lower than in routine scans [ 26 ].…”
Section: Discussionmentioning
confidence: 93%
“…The routine chest CT protocol had been optimized in our radiology center to reduce the radiation dose of COVID-19 patients without reducing its efficiency. Several studies confirmed the effectiveness of low-dose and ultra-low-dose CT scans in detecting and evaluating COVID-19 [ 22 25 ]. Therefore, in pandemics such as COVID-19 where ionizing radiation is employed for screening or follow-up of a large population, radiation settings can be significantly lower than in routine scans [ 26 ].…”
Section: Discussionmentioning
confidence: 93%
“…An optimization study by Niu et al suggests kV = 100 and mAs = 40 for Covid-19 patient's chest CT scans ( Niu et al, 2021 ). In this study, different hospitals used different kV and mAs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pitch number, some studies suggest a pitch of less than 1 to have an image with enough quality to detect the ground-glass nodules ( Niu et al, 2021 ). However, other studies used pitch numbers of 1.4 and 1.5 and slice thickness of 5 mm, satisfying the results ( Samir et al, 2021a ; Song et al, 2020 ), similar to the results of H4 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al (67) found that the image quality of the shelter hospital CT (CT Ark) had no obvious difference compared to ordinary CT (Brilliance 64) based on subjective observations. Andrea et al (68) and Niu et al (69) recognized that a low radiation dose could still provide sufficient diagnostic quality to exclude COVID-19. Bernardo et al (70) deemed that there was little difference in the distribution and lobar extent of pulmonary lesions on chest CT despite substantial differences in CT usage.…”
Section: Discussionmentioning
confidence: 99%